Surrounding Rock Damage Characteristics and Support Optimization of Roadway in Soft Gas-Rich Coal Seam Under the Condition of Penetrating Hydraulic Reaming - Han, Xu; Zhang, Kai; Xue, Xinran; Ma, Bailong (Frontiers in Earth Science, 2022)
The support of roadways in soft coal seams is a challenge in deep coal mines. For Gas-rich coal seams, many methods are developed to pre-drainage the gas before mining. The Penetrating Hydraulic Reaming (PHR) is one of the most efficient methods to reduce the gas content and pressure in the coal seams. However, the PHR method will cause many large holes in the coal seam, which brings difficulty to in-seam roadways control. The strength parameters of the coal are essential for roadway stability analysis. However, in soft coal seam, the sampling of the coal is difficult, and the direct evaluation of the coal strength parameters is unfeasible. In the present research, the surrounding rock damage characteristics of the holes induced by PHR are firstly evaluated by Ground Penetrating Radar (GPR). Then, the strength parameters of the coal are determined via back analysis method. After that, the deformation and failure of the roadway is analyzed, and an optimized support scheme is proposed. According to the monitored displacement and measured damage zone of the roadway, the roadway is well controlled by the proposed support scheme.